IDENTIFICATION OF METABOLITE COMPOUNDS IN EXTRACT AND EXTRACT FRACTIONS OF MORINGA LEAVES (Moringa oleifera) USING THIN LAYER CHROMATOGRAPHY (TLC) METHOD - Khairi, Widayatul; Safwan; Hendriyani, Irmatika (Jurnal Biosains Pascasarjana, 2025)
Moringa oleifera, known in Indonesia as "kelor," is often referred to as "the miracle tree" due to its natural nutritional and medicinal properties. Compounds found in Moringa leaf extract have been confirmed to include flavonoids. These compounds contain -OH groups attached to benzene rings, which contribute to their antioxidant, anti-inflammatory, and antimicrobial properties. The aim of this study was to identify secondary metabolites in Moringa leaves using the Thin Layer Chromatography (TLC) method. The results showed that flavonoids, tannins, alkaloids, and saponins were present in the ethyl acetate fraction, while tannins were found in both the extract and aqueous fraction. Additionally, steroids were detected in the n-hexane fraction. In conclusion, Moringa oleifera contains secondary metabolite compounds.